Writing old age and impairments in late medieval England - Rogers, Will (Medievalist) (Borderlines (Leeds, England), 2021)
The old speaker in Middle English literature often claims to be impaired because of age. This admission is often followed by narration that directly contradicts it, as speakers, such as the Reeve in Chaucer's 'Canterbury Tales' or Amans in Gower's 'Confessio Amantis', proceed to perform even as they claim debility. More than the modesty topos, this contradiction exists, the book argues, as prosthesis: old age brings with it debility, but discussing age-related impairments augments the old, impaired body, while simultaneously undercutting and emphasizing bodily impairments. This language of prosthesis becomes a metaphor for the works these speakers use to fashion narrative, which exist as incomplete yet powerful sources.